Characterizing Secondary and Atypical Parkinsonisms: Defining Features and Clinical Variability - Iraís Viveros-Martínez; Cristofer Zarate-Calderon; Donají Chi-Castañeda; Porfirio Carrillo; Gonzalo E. Aranda-Abreu; Armando J. Martínez; Jorge Manzo; Genaro A. Coria; Luis I. García (Neuroglia)
Parkinsonism is a clinical syndrome characterized by akinesia/bradykinesia, muscle rigidity, resting tremor, and postural instability. Within the group of parkinsonisms is Parkinson’s disease, also known as neurodegenerative parkinsonian syndrome. The group of atypical parkinsonisms was established due to the existence of sporadic parkinsonisms that do not share the exact etiology of Parkinson’s disease. Additionally, parkinsonisms that arise from causes other than neurodegeneration have been classified as secondary parkinsonisms. With this in mind, given the diversity of etiologies that can trigger parkinsonism, it is crucial to understand the symptomatology and its relationship with the basal ganglia (including damage to the nigrostriatal pathway, neuroinflammation, and neuronal damage). Only then will it be possible to propose appropriate treatments for each variant of parkinsonism.